2020
DOI: 10.1097/jnn.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

An Expert Patient Program as a Tool to Empower People With Multiple Sclerosis

Abstract: Engaging and empowering people & communities Strategy 2: Strengthening governance & accountability Strategy 3: Reorienting the model of care Strategy 4: Coordinating services within and across sectors Strategy 5: Creating an enabling environment Strategic direction 1: Empowering and engaging people Engaging and empowering individuals and families Bolstering participatory governance Defining service priorities based on life-course needs, respecting social preferences Coordinating care for individuals Strengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Among the potential benefits of this program, we can mention the improvement in knowledge and quality of life and the normalization of people's health. 23 On the basis of this, the use of empowerment programs in people with chronic diseases may lead to greater adaptation of the person to the disease and improvement of the person's living conditions. By designing this program, we were able to improve people's belief in their own abilities (self-efficacy) and improve people's performance.…”
Section: Discussionmentioning
confidence: 99%
“…Among the potential benefits of this program, we can mention the improvement in knowledge and quality of life and the normalization of people's health. 23 On the basis of this, the use of empowerment programs in people with chronic diseases may lead to greater adaptation of the person to the disease and improvement of the person's living conditions. By designing this program, we were able to improve people's belief in their own abilities (self-efficacy) and improve people's performance.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 26 By focusing on coordinating the care of MS patients throughout the disease trajectory, nurses can capture different types of information and support neurologists in the treatment decision-making process. 5 , 6 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Our research could be used to develop interventions where the areas emotional, work, social interaction and lifestyle, physical aspects of life and the medical context could be focused on . Sanchez et al 34 identified needs and demands of people with MS as well. They could show the importance of empowering people with MS.…”
Section: Discussionmentioning
confidence: 99%